Women's Representation in the 2018 United States Midterm Elections - Yasinta Widya Prameswari; Agus Trihartono; Abubakar Eby Hara (Journal of Feminism and Gender Studies, 2023)
United States politics is a difficult arena to reach for women due to the high levels of gender discrimination and sexism. A new history came up on their midterm election on Tuesday 6th November 2018. Due to the record number of women who passed and running for office, also the surge in activism was higher than previos years. The number of female legislator is 23.4% for the House of Representative and 25% for Senate. This record number is the highest one in United State politic history of women representation. The process of increasing women’s representation in 2018 midterm election to some extent influenced by the paradigm shifting of the women’s movement.